Insight in Obsessive-Compulsive Disorder: Relationship With Sociodemographic and Clinical Characteristics. Issue 6 (November 2021) - Guillén-Font, M. Asunción; Cervera, Mònica; Puigoriol, Emma; FOGUET-BOREU, QUINTÍ; Arrufat, Francesc X.; Serra-Millàs, Montserrat
Abstract : Insight is considered a multidimensional concept and, in the context of obsessive-compulsive disorder (OCD), impairment in insight has been widely reported to be associated with severity and other clinical and sociodemographic variables. However, the studies concerning insight in OCD have produced heterogenous data as a result of the scales used to measure insight. To overcome this heterogeneity, the study presented here used 4 different widely used and validated insight scales. The objective was to evaluate various aspects of insight using these scales to identify the relationships between different aspects of insight and clinical and sociodemographic variables to assess which scale or scales might possess greater efficiency in clinical practice. For this purpose, a descriptive, observational, and cross-sectional study of 81 patients in treatment in a mental health center was conducted. Patients were evaluated using the Brown Assessment of Beliefs Scale, the Overvalued Ideas Scale, the Scale of Unawareness of Mental Disorders, the Yale-Brown Obsessive Compulsive Scale, the Clinical Global Impressions Scale, the Global Assessment of Functioning Scale, and the Rey-Osterrieth Complex Figure Test. The results reported significant relationships between insight and scores on the Yale-Brown Obsessive Compulsive Scale (Thoughts, Compulsions, and Total scales), Clinical Global Impressions Scale, and the Global Assessment of Functioning Scale, and significant differences with regard to sex, level of education, working status, and course of the disorder. A correlation analysis was conducted to assess the relationships among the 4 insight scales. The results of this analysis suggest that the scales that measure insight in a multidimensional way (Brown Assessment of Beliefs Scale and Overvalued Ideas Scale) provide more information about the severity of the disorder in patients with OCD.